Cyclicity in ontogeny and age determination of Flexopecten glaber (Bivalvia, Pectinidae) in the Black Sea - Igor P. Bondarev (Nature Conservation Research: Заповедная наука)
Flexopecten glaber is an actively fished species in the Mediterranean Sea and a promising candidate for mariculture in the Black Sea. Flexopecten glaber is included in the Red Data Books of the Republic of Crimea and Sevastopol city as a species declining in number (Category 2). In this study, over 1500 specimens sampled near the Crimean Peninsula between 2017 and 2023 were analysed to investigate the ontogeny of F. glaber and develop a method for determining individual age, based on the relationship between stages of gonadal development and changes in shell surface morphology. The cyclicity of development was assessed by comparing the cycles of gonad formation with the features of the surface morphology of the shell. A correlation was found between the morphology of the surface of shell valves and the stages of the annual cycle of gonad development. On this basis, a scheme for determining the developmental stages and individual age of F. glaber specimens from the morphology of shell valves has been developed. The most prominent mark on the shell surface is formed mainly in winter as a result of the physiological restructuring of the organism before the beginning of the annual cycle of gonad formation. However, to determine the age of F. glaber, the spawning marks formed mainly in summer need to be considered. The proposed scheme for determining the developmental stages and age of F. glaber individuals is a valuable tool for studying the species and can help resolve a variety of ecological and conservation issues.